DEVELOPMENT OF COD (CHEMICAL OXYGEN DEMAND) ANALYSIS METHOD IN WASTE WATER USING SPECTRODIRECT - Ade Heri Mulyati; Leny Heliawati; Sutanto .; Uswatun Hasanah; Diana Widiastuti; Siti Warnasih; Yulian Syahputri (Journal of Science Innovare, 2020)
Increased human activities will cause various problems, one of which is water pollution in water sources because it receives a pollution load that exceeds its carrying capacity. In the context of environmental conservation, the government has set quality standards for liquid waste produced by various industries and other activities in a Decree of the State Minister for the Environment. COD (Chemical Oxygen Demand) is one of the most important parameters in wastewater quality standards. This study aims to validate the COD analysis method which refers to COD Thermoreactor System (LOVIBOND brand) at Pakuan University Service Laboratory, to ensure the validity of COD analysis results at Pakuan University Service Laboratory. Spectrodirect COD analysis method provides results that meet the requirements of accuracy, precision, LOD, and LOQ which is quite good. The results of the Coefficient of Variation give good results with a value of 1.8841% indicating the accuracy of the analysis method is good. The accuracy parameter also gives good results and meets the requirements with a% recovery value of 98.70351%. Overall, it can be stated that the spectrodirect analysis method tested is an accurate, precise, simple, and economical method for determining COD levels